EKSEKUSI TINDAK PIDANA PERJUDIAN (MAISIR) DI MAHKAMAH SYAR’IYAH LHOKSEUMAWE - Zul Akli (Jurnal Ilmu Hukum, 2013)
Article 5 Qanun No. 13 of 2003 onGambling (Gambling) states "Everyperson prohibited from gamblingact". Furthermore, in the explanationof Qanun No. 13 of 2003 states thatthe prohibition of gambling Qanunareintendedtopreemptive,preventive, and at its optimum levelRemedium as repressive effortsthrough the imposition of 'uqubat inthe form of' uqubat ta'zir which canbe either 'uqubat whip and' uqubatfines (gharamah). Syari'yah Court inthe Province of Aceh is a special courtin the religious courts throughout thejudicial authority regarding theauthority of religion and is a specialcourt in general courts throughoutthe judicial authority of the publicauthority concerned.Keywords : Ekseksekusi, Maisir, Mahkamah Syar’iyah.